Neurovascular EGFL7 regulates adult neurogenesis in the subventricular zone and thereby affects olfactory perception - Frank Bicker (Nature Portfolio, 2017)
The vascular stem cell niche regulates the proliferation and differentiation of neural stem cells (NSCs) in the adult subventricular zone. Here the authors identify EGFL7 as a neurovascular regulator of NSCsin vivo; EGFL7-knockout mice show reduced neurogenesis, and exhibit impaired olfactory perception and behaviour.